2014
DOI: 10.1080/09645292.2014.966062
|View full text |Cite
|
Sign up to set email alerts
|

Risky business: an analysis of teacher risk preferences

Abstract: A range of proposals aim to reform teacher compensation, recruitment, and retention. Teachers have generally not embraced these policies. One potential explanation for their objections is that teachers are relatively risk averse. We examine this hypothesis using a risk-elicitation task common to experimental economics. By comparing preferences of new teachers with those entering other professions, we find that individuals choosing to teach are significantly more risk averse. This suggests that the teaching pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 26 publications
(26 reference statements)
1
26
0
Order By: Relevance
“…Moreover, Bowen et al (2015) find that graduate students in teacher education programs are more risk-averse, on average, than graduate students in business administration or law.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Moreover, Bowen et al (2015) find that graduate students in teacher education programs are more risk-averse, on average, than graduate students in business administration or law.…”
Section: Introductionmentioning
confidence: 97%
“…Due to the link between risk aversion and the preference for payment schemes, teachers' risk attitude isfor examplean important factor to consider when designing teacher payment reforms. In particular, risk-averse teachers can be expected to be resistant to performance pay (Bowen et al 2015). Performance pay would likely reduce teachers' satisfaction if they are risk-averse and -insofar as teachers' higher risk aversion is a selection effectperformance pay would attract a differently motivated workforce to the teaching profession (Dohmen and Falk 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, public sector pay researchers could begin to consider whether PFP influences employee sorting along important personality dimensions that have long been of interest to scholars and practitioners in the closely related field of human resource management, such as employee risk aversion. In a series of laboratory experiments, Bowen et al () and Bowen and Mills () found evidence that teachers are generally more risk averse than comparable nonteacher professionals and that the most risk‐averse teachers prefer working under fixed (e.g., rigid) salary schedules rather than variable‐pay (e.g., pay‐for‐performance) systems. In cases in which government agencies (public employers) wish to attract and hire employees who are more willing to take risks, understanding whether PFP—and variable pay more generally—can improve attraction and/or reduce attrition among less risk‐averse employees would seem to be a particularly fruitful line of inquiry.…”
Section: Discussionmentioning
confidence: 99%
“…Once a field gains a reputation for low cognitive ability, it attracts new entrants who do not value intelligence, starting with who chooses education as a college major (Armstrong and Hamilton 2013;Stotsky 2015;Wai 2015). Further, school leaders rarely terminate teachers for poor teaching (Moe 2011) and likely as a result, the field attracts the risk averse (Bowen et al 2015). Stotsky (2015) argues that, in part, reducing the rigor of teacher certification tests like the Praxis reflects the desire for a racially diverse teaching core.…”
Section: Observesmentioning
confidence: 99%